2014
DOI: 10.1016/j.rmed.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin cough threshold test in diagnostics

Abstract: For patients with SHR and chronic cough, capsaicin cough sensitivity was once again confirmed to be increased, in this case, using the single-breath dose-response method. Limits set for cough reactions regarded as more sensitive than normal can be useful in diagnostics and further research. C5 seems to be the best measure to use in research and differential diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 39 publications
1
29
1
2
Order By: Relevance
“…Emax needs to be evaluated in larger numbers of subjects to confirm the findings of this preliminary study. A tidal breathing method delivering capsaicin has also been reported to discriminate patients with cough well from healthy controls [37]. C5 was superior than C2 for this purpose.…”
Section: Cough Reflex Sensitivity Challenge Testsmentioning
confidence: 99%
“…Emax needs to be evaluated in larger numbers of subjects to confirm the findings of this preliminary study. A tidal breathing method delivering capsaicin has also been reported to discriminate patients with cough well from healthy controls [37]. C5 was superior than C2 for this purpose.…”
Section: Cough Reflex Sensitivity Challenge Testsmentioning
confidence: 99%
“…At each visit, cough sensitivity was assessed by a standardized capsaicin inhalation cough test using the threshold method [29], following the recommendations in the European Respiratory Societies (ERS) guidelines [30]. They also answered questionnaires relating to cough and completed a daily "patient cough and symptom diary".…”
Section: Methodsmentioning
confidence: 99%
“…Capsaicin solutions were administered from a compressed airedriven side-stream nebulizer (MedicAid Pro, Sussex, UK) controlled by an aerosol provocation system (APS version 5.02 software, Viasys Healthcare GmbH, Hoechberg, Germany). Double concentrations were given at 1-min intervals, and the concentration of capsaicin causing two (C2) and five (C5) coughs during the 1-min period between each dose was registered [29]. The participants were not informed that the cough thresholds were the endpoints of the provocation.…”
Section: Capsaicin Provocationmentioning
confidence: 99%
“…In this study, 353 IGRA-negative patients were commenced on TNF-α antagonists for a variety of inflammatory conditions without further LTBI assessment; one patient subsequently developed active TB. This approach differs from our practice, we currently advocate a "triple testing" approach in all patients referred for LTBI screening with a combination of risk stratification according to the British Thoracic Society (BTS) guidelines [2], tuberculin skin test (TST) and IGRA (T-Spot.TB: Oxford Immunotec, Oxford, UK) to aim for maximum sensitivity. We have previously published an evaluation of this approach in 137 patients receiving immunosuppression and found that 111 (81.0%) were IGRA negative [3].…”
Section: Screening For Latent Tuberculosis Before Tumour Necrosis Facmentioning
confidence: 99%
“…First, cough challenge which was initially used in 1954 and although refined has not entered routine clinical practice since it does not differentiate health from disease with sufficient discrimination (an optimist would say we have yet to find the right challenge). However, challenges are clearly of use in phenotyping patients [2], assessing tussive mechanisms and clarifying target engagement for therapies directed at specific channels. Secondly, various subjective measures for assessing quality of life and cough-related symptoms have been developed.…”
mentioning
confidence: 99%